TINDAK PIDANA PENIPUAN TERKAIT DENGAN IKLAN PENJUALAN BARANG YANG MERUGIKAN KONSUMEN - Julieta Santi Simorangkir; Syafruddin Kalo; Muhammad Hamdan; Dedi Harianto (USU LAW JOURNAL, 2016)
ABSTRACT Meet their needs, consumers are faced with various types of products offered by businesses. With the various types of products and freedom for consumers to choose a variety of products offered lead to competition among businesses. Competition among businesses to market products that offer the consumer interest can be done in various ways, one of them promoting products through print media advertisements. Advertising is a tool for businesses to introduce their products to the public in order to influence the tendency for people to use or consume. The problem is, the ad does not always give a true or deceptive information about an advertised product, so that consumers can be harmed by the behavior. If perpetrators of this background can be formulated several problems, namely how the forms of advertising fraud that harm consumers, whether fraud ad meets the elements of a crime, how to determine the criminal liability for those who make advertising the sale of goods that harm consumers in Indonesia based on the Code of Criminal Law and Law 8 of 1999 on Consumer Protection.  Keywords : Ad Fraud, Liability Business Communities Ad, Ad Adverse Consumers.